Alcohol-induced changes in the phospholipid molecular species of Escherichia coli. - Berger, B (1980)
In Escherichia coli, the additon of ethanol resulted in the synthesis of an increased proportion of phospholipids containing two unsaturated fatty acids. The addition of hexanol resulted in the opposite effect, an increase in the proportion of monounsaturated molecular species. The alcohol-induced changes were quantitatively similar to those caused by changing growth temperature. These results suggest that both adaptation to temperature and alcohol-induced changes in lipid composition share some common regulatory features.